Benefits management in office fit-out projects - Baccarini, David; Bateup, G. (Emerald Group Publishing Ltd., 2008)
Purpose - The purpose of this paper is to investigate how benefits management is applied to office fit-out projects, in terms of benefits identification, benefits planning, benefits control and benefits realisation. Design/methodology/approach - Three case studies, based in Perth (Western Australia) are investigated based on structured interviews with the project sponsor; and analysis of secondary documentation, such as business cases, briefs, and post-occupancy evaluations. Findings - There is no coherent, holistic application of benefits management models in office fit-out projects. There are fragments of benefits management evident from the research, such as benefits identification and planning within business cases and briefs, and benefits realisation through post-occupancy evaluations. Research limitations/implications - The research is based on three case studies, so it is not possible to draw any strong generalisations. Future studies are needed to corroborate or contradict the findings in this research. Practical implications - The results highlight some aspects of benefits management in office fit-out projects that could be improved, particularly the setting of key performance indicators for benefits, and more formal benefits control and realisation processes. Originality/value - This research is the first to take the construct of benefits management, which is primarily applied to information systems projects, and investigate its application in building projects. © Emerald Group Publishing Limited.